2018
DOI: 10.3390/children5070090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Couple Relationship Dynamics among Low-Income Parents in a Relationship Education Program Are Associated with Decreases in Their Children’s Mental Health Symptoms

Abstract: Witnessing intimate partner violence (IPV) among parents negatively impacts millions of children in the United States each year. Low-income families are disproportionately affected by IPV compared to middle- and high-income individuals, and are beginning to be the focus of IPV secondary prevention interventions, including relationship education programs. Despite these developments, few studies have examined changes in psychosocial functioning among children of parents participating in relationship education pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
(70 reference statements)
1
8
0
1
Order By: Relevance
“…Treatment group participants reported significantly better parent–child relationships than wait-list control participants 3 months after random assignment. This finding aligns with previous research that demonstrated positive outcomes for parents attending relationship education (Kirkland et al, 2011; Sterrett-Hong et al, 2018). Through enhancements in the parent–child relationship, indirect outcomes are likely (i.e., increased self-esteem, increased decision-making skills, empathy; Landreth & Bratton, 2020; Siegel & Bryson, 2019), resulting in overall increased mental health for children.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Treatment group participants reported significantly better parent–child relationships than wait-list control participants 3 months after random assignment. This finding aligns with previous research that demonstrated positive outcomes for parents attending relationship education (Kirkland et al, 2011; Sterrett-Hong et al, 2018). Through enhancements in the parent–child relationship, indirect outcomes are likely (i.e., increased self-esteem, increased decision-making skills, empathy; Landreth & Bratton, 2020; Siegel & Bryson, 2019), resulting in overall increased mental health for children.…”
Section: Discussionsupporting
confidence: 92%
“…Security within this primary relationship often precedes a child’s increased self-regulation, increased decision-making abilities, and increased empathy between parent and child, thus mitigating long term mental health concerns (Landreth & Bratton, 2020; Siegel & Bryson, 2019). Previous researchers indicated that parents participating in relationship education demonstrated improvements in parent–child relationships and noted decreases of child mental health difficulties within low-income families (Kirkland et al, 2011; Sterrett-Hong et al, 2018). Additionally, couples-oriented relationship education demonstrated positive effects for increasing parental alliance (Carlson, Barden, et al, 2014) and parental attitudes (Barden et al, 2015).…”
Section: Family Relationships For Economically Vulnerable Parentsmentioning
confidence: 99%
“…Evidently, these can lead to the intervention of social services and the removal of the child or adolescent from the family [19]. In Portugal, the main factors that lead to institutionalisation are parental neglect and abandonment, physical and/or psychological abuse, and the existence of high-risk disruptive behaviour [12].…”
Section: Children and Adolescents In Institutional Carementioning
confidence: 99%
“…Children and adolescents who suffer abuse or who live under circumstances of intrafamily violence experience severe and acute stress, and therefore they tend to develop post-traumatic stress disorder. This is usually expressed in the form of emotional and behavioural disturbances and difficulties in interpersonal functioning [11][12][13][14][15]. In this regard, decades of research on psychosocial adversity in childhood, and particularly on child abuse, have produced sufficient evidence to conclude that abuse affects a child's developmental path, with consequences that can continue throughout life [16].…”
Section: Introduction 1psychosocial Adversity Psychopathological Problems and Resilience Assets In Children And Adolescentsmentioning
confidence: 99%
“…That meant an increase in positive behaviors and a decrease in negative behaviors were related to the improvement of the relationships. In another couple relationship education program, changes in parent-child relationship quality were associated with changes in parents' conflict-related behaviors and mediated the associations between changes in couples' relationship quality and changes in a child's mental health symptoms [33]. These studies focused on the improvement of relationship quality, while they were all conducted among general population.…”
Section: Introductionmentioning
confidence: 99%